2005
DOI: 10.1002/clc.4960280905
|View full text |Cite
|
Sign up to set email alerts
|

High-sensitivity C-reactive protein as a risk assessment tool for cardiovascular disease

Abstract: Summary: Almost half of first cardiovascular events occur in individuals with no known risk factors. Attempts in the last decade to predict cardiovascular risk more accurately have led to the emergence of a novel risk factor, C-reactive protein (CRP), which has proved to be as good a risk predictor as lowdensity lipoprotein cholesterol. C-reactive protein is an index of inflammation that is now believed to promote directly all stages of atherosclerosis, including plaque rupture. As measured by high-sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 38 publications
5
51
0
1
Order By: Relevance
“…The present study indeed demonstrated that pioglitazone-induced increase in adiponectin was associated with a significant decrease in hsCRP, which has been implicated in a valuable marker for atherosclerosis [21][22][23]. This anti-inflammatory effect may play a crucial role in preventing the development of atherosclerosis and cardiovascular disease.…”
Section: Discussionsupporting
confidence: 72%
“…The present study indeed demonstrated that pioglitazone-induced increase in adiponectin was associated with a significant decrease in hsCRP, which has been implicated in a valuable marker for atherosclerosis [21][22][23]. This anti-inflammatory effect may play a crucial role in preventing the development of atherosclerosis and cardiovascular disease.…”
Section: Discussionsupporting
confidence: 72%
“…When measured with new high-sensitivity assays, the levels of CRP have proven to predict future cardiovascular risk. Among apparently healthy men and women, the levels of high-sensitivity-CRP (hs-CRP) of !1, 1-3 and O3 mg/l distinguish between those at low, moderate and high risk of future cardiovascular disease (4).…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Evidence also implicates CRP, and thus inflammation, as a useful clinical measure for identifying risk of developing the insulin resistance syndrome, particularly in women. 14,15 Serum CRP concentrations correlate positively with abdominal obesity, hyperinsulinemia, and other components of the insulin resistance syndrome. Nevertheless, associations of CRP with insulin resistance independent of obesity suggest that divergent pathways linking inflammation and insulin resistance are of importance, especially among nonobese individuals.…”
mentioning
confidence: 99%